Spanish Spaces : Landscape, Space and Place in Contemporary Spanish Culture. - Davies, Ann (Contemporary Hispanic and Lusophone Cultures, 6., 2012)
Spanish Spaces is a pioneering study that marries cultural geography with contemporary Spanish culture. It consists of thematic case studies (memory and forgetting, nationalism and terrorism, crime and detection, gender, tourism and immigration), selected for their currency and drawing on the exploration of these themes in contemporary Spanish film and literature. Throughout the chapters the author investigates what it means to think of space and place in specifically Spanish terms.